Freshwater fish richness baseline from the São Francisco Interbasin Water Transfer Project in the Brazilian Semiarid - Silva,Márcio J. (2020)
Abstract Among Neotropical freshwater ecoregions, the Mid-Northeastern Caatinga (MNCE) is a fish knowledge gap. Its temporary drainages are receptors of the São Francisco interbasin water transfer project (SFR-IWT) in the Brazilian semiarid. We provide a comprehensive baseline of fish richness of the five SFR-IWT basins. Species richness, shared, endemic, threatened and non-native species were obtained using sampling, ichthyologic collections, literature and online repositories (306 localities). In total 121, species were recorded, 111 of them native, and 16 (14.41%) listed for all basins. Higher richness of native species (78, 70.27%) was recorded in the São Francisco lower-middle stretch (SFRE), including 23 endemic, 61 (54.95%) in MNCE basins (13 endemic), and 28 (25.23%) shared between both ecoregions. In the MNCE, 50 species were recorded in Jaguaribe (JAG), 39 in Piranhas-Açu, 36 in Paraíba do Norte, and 32 in Apodi-Mossoró (APO). The number of species shared between the SFRE and each receptor basin varied from 24 (23.08%, JAG) to 20 (22.22%, APO). JAG contains 81.97% of the receptor basins’ species. Its higher richness and endemism deserve special attention regarding the ongoing hydrological changes. This study will help detect possible modifications in the ichthyofauna of the main MNCE drainages.